Effect of surface air cooling on the high frequent cyclic ablation of C/C–SiC–ZrB2–ZrC composite under ms-scale single loading. (September 2022) - Feng, Wei; Han, Qinxin; Liu, Lei; Chen, Jian; Yao, Xiaofei; Yao, Xiyuan; Tian, Yunlong; Shi, Haotian
Abstract: Influence of surface air cooling on the high frequent cyclic ablation of layer-structural C/C–SiC–ZrB2 –ZrC composite was mainly studied. Tests were performed by alternant plasma and surface cooling airflow for 200 cycles under ms-scale single loading. The C/C–SiC–ZrB2 –ZrC composite displayed good ablation resistance. And the ablation rates decreased firstly and then rose up with increasing of the airflow rate from 0 to 4 m 3 /h, whereas the highest surface temperature presented an inverse relationship. The lowest ablation rates were 0.12 μm/s and 0.038 mg/s under surface airflow of 2 m 3 /h. Morphologies and phases of the ablated surface indicated that the low-speed airflow was helpful to the spread out and accumulation of the ablation products whereas the stronger airflow caused surface cracks and fragments of the composite. The intensities of the mechanical erosion under different surface air cooling dominated the high frequent cyclic ablation behavior. Highlights: Effect of surface air cooling was studied under high frequent cyclic ablation. Two scale layer-structural C/C–SiC–ZrB2 –ZrC displayed good ablation property. A low speed airflow was helpful to the accumulation of ablation products.